1999
DOI: 10.1093/oxfordjournals.schbul.a033389
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Complications of Pregnancy and Labor: An Individual Patient Data Meta-analysis

Abstract: Several epidemiological studies have reported an association between complications of pregnancy and delivery and schizophrenia, but none have had sufficient power to examine specific complications that, individually, are of low prevalence. We, therefore, performed an individual patient meta-analysis using the raw data from case control studies that used the Lewis-Murray scale. Data were obtained from 12 studies on 700 schizophrenia subjects and 835 controls. There were significant associations between schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
4
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(158 citation statements)
references
References 40 publications
(51 reference statements)
9
136
4
9
Order By: Relevance
“…Many studies have shown that the prevalence of obstetric complications is higher in individuals with schizophrenia than in the general population, [1][2][3][4][5][6] which has led to an often-stated, but never empirically tested, theory that serious obstetric complications interact with genetic risk factors to increase risk. 1,5,[7][8][9][10] A recent review by Schmidt-Kastner and colleagues 11 suggested that susceptibility genes for schizophrenia were more likely than randomly selected genes to be regulated by hypoxia/ischemia and/or expressed in the cerebrovasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the prevalence of obstetric complications is higher in individuals with schizophrenia than in the general population, [1][2][3][4][5][6] which has led to an often-stated, but never empirically tested, theory that serious obstetric complications interact with genetic risk factors to increase risk. 1,5,[7][8][9][10] A recent review by Schmidt-Kastner and colleagues 11 suggested that susceptibility genes for schizophrenia were more likely than randomly selected genes to be regulated by hypoxia/ischemia and/or expressed in the cerebrovasculature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DHEA and DHEAS decrease neuronal death following anoxia (Marx et al, 2000b), and obstetrical complications resulting in hypoxia are associated with increased schizophrenia risk (Dalman et al, 2001;Cannon et al, 1999Cannon et al, , 2000Geddes et al, 1999). Allopregnanolone demonstrates anticonvulsant actions in a number of seizure paradigms (Kokate et al, 1994(Kokate et al, , 1996Devaud et al, 1995;Belelli et al, 1989) and exhibits pronounced protective effects against neurodegeneration in a mouse model of Niemann-Pick type C disease .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 854 patients (47.8% with OC) from 11 European research groups showed a significant association between an earlier age of onset of schizophrenia and the presence of OCs, with an odds ratio of 1.52 (95% CI 1.04-2.22) [23]. A further meta-analysis on data obtained from 12 studies of 700 schizophrenic subjects and 835 controls also showed significant associations between schizophrenia and premature rupture of membranes, gestational age less than 37 weeks, and the use of either resuscitation or an incubator [24]. In addition, the North Finland Birth Cohort, a study of 11,017 individuals, has shown a sevenfold excess of perinatal brain defects in subjects with schizophrenia.…”
Section: Environmental Influencesmentioning
confidence: 99%